Morphological variation in five related species of Barleria (Acanthaceae) - Nyirenda, Florence Chisenga (My University, 2013)
Variation has been known to be a result of various causes including plasticity, gene flow or the lack of it. In this work morphological variation exhibited within five species of Barleria (B. bechuanensis C.B. Clarke, B. irritans Nees, B. jubata S. Moore, B. pungens L.f. and B. rigida Nees) was studied to establish whether it was discrete or continuous. Morphological characters were examined and recorded in the form of matrices and photographs. Variation was analysed from three aspects: macro-morphology, micro-morphology and distribution of morphological characters. Cluster analysis imposed a hierarchical non-overlapping association among operational taxonomic units (OTUs) while ordination established whether the variation was discrete or continuous. Cluster analysis and ordination demonstrated that some of the species complexes exhibited discrete variation while others exhibited both continuous and discrete variation. Distribution maps which illustrated the distribution of clusters and some of the morphological characters in geographic space suggested that allopatric, parapatric and / or sympatric speciation could have occurred bringing about the differentiation. Pubescence revealed that trichome morphology and distribution can to some extent be used to define intra-specific variation. On the basis of phenetics analysis, B. jubata is maintained as a single species while the B. bechuanensis and B. irritans complexes are separated into two species each (differentiated by leaf size, shape and margins; and by bracteole size and number of veins in the bracteole respectively). Within the B. rigida complex, two species are recognised where one has lobed bracteoles and calyx lobes and the other has non-lobed bracteoles and calyx lobes. Included within the latter are plants formerly known as B. ilicina (E. Mey. ex T. Anders.). Barleria pungens is separated into two species, one with flat green leaf margins and the other with wavy green or white leaf margins.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science Johannesburg, September 2012.
Keywords: Acanthaceae.